POTENSI EKSTRAK CODIUM, HALIMEDA, DICTYOTA, CHONDRUS, GLACILLARIA SEBAGAI SUMBER PIGMEN DAN ANTIOKSIDAN ALAMI - Tri Saptari Haryani; Uswatun Hasanah; Oom Komala; Intan Lestari; Dina Agustina (Universitas Pakuan, 2022)
Macroalgae is one of the marine biological resources that has an important role in terms of economy, as a source of food and medicine that is beneficial to health. This study aims to determine the source of natural pigments and antioxidants extracts of algae Codium, Halimeda, Dictyota, Chondrus, and Glacillaria using acetone, Folin Ciocalteu, and 1,1-Diphenyl-2-Picrylhydrazil (DPPH) reagents. The method includes sampling, measuring water content by gravimetry, making extracts using maceration method, qualitative phytochemical testing, pigment source test for chlorophyll a, chlorophyll b, total chlorophyll, total phenol, and antioxidant activity. Phytochemical test results obtained that all samples contained flavonoid compounds, alkaloids, while Halimeda and Gracillaria extracts did not have terpenoids. The results of the test for the pigment source were the highest value obtained in Chondrus extract, which was 10.0038 mg/g. And from the results of antioxidant activity testing, all sample extracts were obtained including the group with moderate strength (IC50 value) ranging from 100-500).